Pemberdayaan Guru SD melalui Participatory Action Research dalam Mengoptimalkan Kompetensi Penelitian - Faizah, Silviana Nur; Khairiyah, Ummu; Alawiyin, Mufthi; Maulidiyah, Yunita Nur (LP2M INSURI Ponorogo, 2023)
Teachers are professional educators tasked with carrying out quality learning and developing their professionalism to improve the quality of education. Classroom Action Research (CAR) can be used as a teaching tool in order to overcome learning loss in education during the covid pandemic while at the same time developing professionalism. Theoretical, cognitive and technical knowledge is a source of obstacles for teachers of SDN 1 Sukomulyo in implementing CAR. This problem urges teachers at SDN 1 Sukomulyo to receive CAR training. The Participatory Action Research (PAR) approach is used to find practical solutions to improve teacher problems in CAR. The PAR approach to this community service consists of the following seven steps: 1) Re-mapping and identifying problems with the problems faced by the community, 2) Focus Group Discussion and problem analysis (joint meeting), 3) Preparatory stage for program action according to the results of the problem analysis carried out with the assisted subjects, 4) Program Socialization, 5) Program Implementation, 6) Monitoring, and 7) Program Evaluation. The results of the training showed an increase in pre-training mastery (theoretical, cognitive and technical) of SDN 1 Sukomulyo teachers by 62% in the